Draft Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Volume-IX Hill Areas Government of Assam - Planning Commission (Planning Commission, 1985)
The two Hill Districts of Assam viz. Karbi Amglong fid N.C, Hills District cover an area of 15,212 Sq. Km. area under Karbi Anglong District being 10,122 Sq. Km and that under N.C, Hills District being 4,890 Sq. Km. These areas are land locked. The geo-physical condition is such that the terrain is very difficult and the villages are scattered with spare population separated for away from one another. There is only one Railway line passing through these two Districts connecting Cachar District on the south and Nagaon Districts on the north. During monsoon, very often the train communication remains suspended for a long time disconnecting supply line.
Office of the Development Commissioner for the Hill Areas of Assam